Constitutive modelling of the skin accounting for chronological ageing - Pond, Damien (Centre for Research in Computational and Applied Mechanics (CERECAM), 2017)
The skin is the largest organ in the human body. It is the first line of contact with the outside world, being subject to a harsh array of physical loads and environmental factors. In addition to this, the skin performs numerous physiological tasks such as thermo-regualtion, vitamin D synthesis and neurotransduction. The skin, as with all biological tissue, is subject to chronological ageing, whereby there is a general breakdown of tissue function and a decline in mechanical properties. In addition to this, skin undergoes extrinsic forms of ageing through exposure to external factors such as ultraviolet radiation, air pollution and cigarette smoking. Skin modelling is an area of biomechanics that, although medical in nature, has expanded into areas such as cosmetics, military, sports equipment and computer graphics. Skin can be approximated at the macroscopic continuum scale as an anisotropic, nearly-incompressible, viscoelastic and non-linear material whose material properties are highly dependent on the ageing process. Through the literature, several phenomenologically based models have been satisfactorily employed to capture the behaviour inherent to the skin, but despite the intrinsic link to age, to date no constitutive model for the UV-induced ageing/damage of skin has been developed that is both capable of capturing the material and structural effects, and is embedded in the rigorous framework of non-linear continuum mechanics. Such a mechanistic model is proposed here. The macroscopic response of the skin is due to microscopic components such as collagen, elastin and the surrounding ground substance and the interaction between them. An overview on the structure of the skin helps motivate the form of the continuum model and identifies which aspects of the skin need to be captured in order to replicate the macroscopic response. Furthermore, the ageing process is explored and a firm understanding of the influence of ageing on the substructures is established. Over time, elastin levels tend to decrease which results in a loss of skin elasticity. Collagen levels drop with age, but tend to flatten out which results in an overall increase in skin stiffness and loss of anisotropy. A worm-like chain constitutive model, arranged in an 8-chain configuration, is employed to capture the mechanical response of the skin. The use of such a micro-structurally-motivated model attempts to connect the underlying substructures (collagen, elastin and ground substance) present in the skin to the overall mechanical response. The constitutive model is implemented within a finite element scheme. Simple uniaxial tests are employed to ascertain the validity of the model, whereby skin samples are stretched to elicit the typical anisotropic locking response. A more complex loading condition is applied through bulge tests where a pressure is applied to an in vitro skin specimen. This more complex test is subsequently used to conduct a series of ageing numerical experiments to ascertain the response of the model to changes in material properties associated with ageing. A modified model is then proposed to capture the ageing response of the skin. The key microscopic biophysical processes that underpin ageing are identified, approximated and adapted sufficiently to be of use in the macroscopic continuum model. Aspects of open-system thermodynamics and mixture theory are adapted to the context of ageing in order to capture a continuous ageing response.